Correlation between Salivary Cotinine Levels and Cigarette Smoking with Recurrent Aphthous Stomatitis - Raghad H Al-Ani; Ashwak Waheeb Shaker; Luma Musa Ibrahim (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Recurrent aphthous stomatitis (RAS) is a widespread oral mucosal disease typified by thepresence of a yellowish-grey base with high margins and flanked by an erythematous halo. RAS typicallycrops up in the lining or nonkeratinized mucosa. It has been found that smoking and salivary cotinine (ametabolic product of nicotine) levels have a protective effect against the occurrence of RAS by increasingkeratinization of the oral mucosa.Objectives: To identify the effect of smoking and nicotine level on the occurrence of RAS.Patients and Methods: the study was conducted on 92 male students studying at different Universities ofBaghdad, Iraq, in the period between January to December 2018. The students were thoroughly questionedabout the yearly recurrence rate and healing period of RAS. Data about smoking history; method, averagedaily dose, and period of the behaviour were recorded for each student. Salivary Cotinine levels weremeasured by the Human Cotinine ELISA Kit and utilising the competitive ELISA technique based on theprotocol of the manufacturer salimetrics assay #1-2002.Results: The study subjects comprised of 92 male students. Their ages were from 18 to 25 years; theaverage age was 21.04 ± 2.2. Forty-two of them were light smokers, and 50 were heavy smokers. They weresubdivided into subgroups according to the duration of smoking (less or more than five years). The annualrecurrence rates and healing period were lower in those who smoked for more than five years than those whosmoked for less than five years with a significant difference in light smokers. Salivary cotinine levels weresignificantly higher in a heavy smoker than in light smokers. Period of healing and yearly recurrence rateswere significantly lower in those who had salivary cotinine level more than 200ng/ml than in those with alevel.Conclusion: The protecting impact of smoking on RAS was solely identified when individuals were heavysmokers or smoked for longer durations of time and correlated with cotinine levels, according to the availableliterature.